A case of a heterozygous ABCC6 mutation showing recurrent ischemic strokes and intracranial hemorrhages. Issue 2 (4th February 2022) - Nomura, Emi; Kawahara, Yuko; Omote, Yoshio; Takahashi, Yoshiaki; Matsumoto, Namiko; Ikegami, Ken; Takemoto, Mami; Hishikawa, Nozomi; Nakano, Yumiko; Yunoki, Taijun; Morihara, Ryuta; Uemura, Masahiro; et al.
Abstract: Mutations in the ATP‐binding cassette subfamily C member 6 ( ABCC6 ) gene are responsible for pseudoxanthoma elasticum (PXE). PXE is a rare genetic metabolic disease with autosomal recessive inheritance that shows ectopic mineralization in skin, eyes, and blood vessels and causes cerebrovascular disease. There are few reports of intracranial hemorrhages in patients with the ABCC6 mutation. We report the first Japanese case with a heterozygous ABCC6 mutation displaying recurrent ischemic strokes and intracranial hemorrhages. We propose that the ABCC6 mutation may be one cause of neurovascular diseases with a family history.